Are There Differences in Anti-Gay Beliefs Among U.S. Veterans and Non-Veterans? Results from the General Social Survey. Issue 10 (23rd August 2020) - Blosnich, John R.; Shipherd, Jillian C.; Kauth, Michael R.
ABSTRACT: Only since 2011 have sexual minorities been able to serve openly in the U.S. military. The previous anti-gay policies and culture of the military may have increased anti-gay beliefs among veterans. Using data from the 2010–2016 General Social Survey, we tested whether veterans more frequently endorsed anti-gay beliefs than their non-veteran peers. Adjusting for sociodemographic characteristics with multiple logistic regression, we tested the associations of veteran status with five anti-gay beliefs (i.e., disallowing a gay person (1) from publicly speaking or (2) teaching at a university, (3) removing a gay-supportive book from a library, (4) whether same-sex sexual relations are wrong, and (5) support of same-sex marriage. Veteran status was associated with greater disagreement with same-sex marriage ( B = 0.16, p = 0.033) but not with other anti-gay beliefs. Most anti-gay beliefs among veterans were explained by other sociodemographic factors and may not be inherent to veteran status.